2022
DOI: 10.3390/coatings12060740
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Yttrium Oxyfluoride Coating with Modified Precursor Solution for Laser-Induced Hydrothermal Synthesis

Abstract: In the semiconductor manufacturing process, the inner walls of the equipment are coated with yttrium-based oxides for etch resistance against plasma exposure. Yttrium oxyfluoride (YOF) particle synthesis and coating methods have been actively studied owing to their high erosion resistance compared to Y2O3 and Al2O3. Owing to the formation of a rough and porous coating layer by thermal spray-coating, the coating layer disintegrates, as the etching process has been conducted for a long time. Laser-induced synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The photoheat generated by the laser on the substrate in the liquid precursor improves the adhesion of the HA coating through precipitation and growth of HA, and increases the corrosion resistance and cell adhesion of the substrate. In addition, various coating layers can be formed depending on the substate and solution used [19,20]. In previous studies that used Mg as the substate, Mg(OH) 2 is formed through a natural reaction in an aqueous solution, and Mg(OH) 2 can supply OH-that can form the HA surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photoheat generated by the laser on the substrate in the liquid precursor improves the adhesion of the HA coating through precipitation and growth of HA, and increases the corrosion resistance and cell adhesion of the substrate. In addition, various coating layers can be formed depending on the substate and solution used [19,20]. In previous studies that used Mg as the substate, Mg(OH) 2 is formed through a natural reaction in an aqueous solution, and Mg(OH) 2 can supply OH-that can form the HA surface.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that surface coating does not occur with too weak laser pulses (5 and 10w) during the LISSC process. It was also observed that a solution which is a combination of NaF and HMTA was required for coating to be formed [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation